Diurnal variability of cerebral metabolites in healthy human brain with 2D localized correlation spectroscopy (2D L‐COSY). Issue 2 (10th January 2019) - Arm, Jameen; Al‐iedani, Oun; Lea, Rod; Lechner‐Scott, Jeannette; Ramadan, Saadallah
Abstract : Background: Two‐dimensional localized correlation spectroscopy (2D L‐COSY) is a research tool that has been applied to evaluate in vivo metabolic activity in many neurological and oncological disorders. Circadian mediators such as brain temperature, hydration, and osmotic regulation have been claimed to change metabolic profiles. Purpose: To evaluate the diurnal variability of neuro‐metabolites with 2D L‐COSY in healthy subjects using a 3 T scanner. Study Type: Crossover. Population/Phantom: Ten healthy subjects and magnetic resonance spectroscopy‐high definition (MRS‐HD) sphere or "Braino." Field Strength/Sequence: 3 T/2D L‐COSY MRS. Assessment: In vivo 2D L‐COSY measurements were performed on ten healthy subjects (5 M/5F, mean age 36.1 ± 7.7 years) repeatedly at three timepoints (0700, 1200, and 1700) on the same day. in vitro evaluations were performed in a similar fashion as in vivo on Braino containing selected brain metabolites at physiological concentrations and pH. 2D L‐COSY was acquired from a 27 cm 3 voxel located in the posterior cingulate cortex. A total of 75 resonances were included in the analysis and spectral peak volumes were normalized to creatine. Statistical Test: One‐way repeated measured analysis of variance with Bonferroni post‐hoc adjustment using SPSS software. Results: In vitro data showed no statistically significant differences between different scans ( P > 0.12). in vivo results showed statistically significant diurnal variations ( P ≤ 0.05, F > 3.88) for 22 resonances. Bonferroni post‐hoc testing showed there was statistically significant increases in metabolite ratios between 0700 and 1700 and these include different moieties of N‐acetylaspartate, creatine, choline, myo‐inositol, lipids, fucose, glutathione, and homocarnosine. Data Conclusion: 2D L‐COSY can detect diurnal physiological variability in neuro‐metabolite levels. Thus, time of the day should be considered when planning MRS studies to avoid confounding results. Level of Evidence : 1 Technical Efficacy Stage : 1 J. Magn. Reson. Imaging 2019;50:592–601.